1989
DOI: 10.1530/acta.0.1200519
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide in pregnant and lactating goats

Abstract: Abstract. Plasma concentrations of atrial natriuretic peptide (ANP) were measured in 6 goats during pregnancy, lactation and a nonpregnant, nonlactating (= control) period before and during a rapid iv load of 0.9% NaCl. The volume of the load was 20% of blood volume. The infusions increased central venous pressure by 7 ± 1 mmHg during pregnancy and 8 ± 1 mmHg during lactation. Before infusions plasma ANP concentrations were 5.7 ± 0.7 pmol/l (control period), 10.8 ± 1.8 pmol/l (pregnancy;P< 0.05),and6.5 ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…This plasma volume expansion of pregnancy also occurs in animal models and is the result of net, continual renal sodium and fluid retention (1). Previous findings in our laboratory and others have indicated that in normal pregnancy the natriuretic response to atrial natriuretic peptide (ANP) is blunted, therefore promoting sodium retention and plasma volume expansion (7,12,15,16).ANP signals through the second messenger cGMP, and we have reported that PDE-5 activity and protein abundance in the inner medullary collecting duct are selectively increased in normal pregnancy (14). In addition, selective, intrarenal PDE-5 inhibition with sildenafil reverses the blunted response to infused ANP seen in normal pregnancy (10).…”
mentioning
confidence: 76%
“…This plasma volume expansion of pregnancy also occurs in animal models and is the result of net, continual renal sodium and fluid retention (1). Previous findings in our laboratory and others have indicated that in normal pregnancy the natriuretic response to atrial natriuretic peptide (ANP) is blunted, therefore promoting sodium retention and plasma volume expansion (7,12,15,16).ANP signals through the second messenger cGMP, and we have reported that PDE-5 activity and protein abundance in the inner medullary collecting duct are selectively increased in normal pregnancy (14). In addition, selective, intrarenal PDE-5 inhibition with sildenafil reverses the blunted response to infused ANP seen in normal pregnancy (10).…”
mentioning
confidence: 76%
“…However, other evidence suggests that a refractoriness develops to ANP that would allow the antinatriuretic RAAS to predominate. For example, the natriuretic response to infused ANP is blunted in pregnant goats (24). We have previously reported that the conscious, chronically catheterized pregnant rat becomes refractory to the tubular natriuretic (but not hemodynamic) actions of ANP (18).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating ANP levels during normal pregnancy in the rat [18,27], goat [32], and human [33] have been reported by several authors. During pregnancy, the plasma ANP level has been suggested to undergo a gradual increase due to increased blood volume and cardiac output [33].…”
Section: Discussionmentioning
confidence: 84%
“…Further, alteration in atrial stretch, such as those induced by acute blood volume expansion, stimulates the secretion of ANP from the mammalian cardiac atria [19,20,35]. Therefore, several investigators have suggested that the release of ANP was accelerated by blood volume expansion and distension of the cardiac atria during pregnancy [9,25,32,33,40], and have postulated a rise in plasma ANP levels during pregnancy that would parallel the known changes in blood volume. However, the present findings were not consistent with this postulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation